Analisis Perbandingan Pelayanan Jasa Warehousing Pada PT. Big Ocean Transportama, PT. Buana Jaya Cargo Dan PT. Cipta Krida Bahari Di Jakarta Tahun 2023 - Akbar Prakoso (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
Big Ocean Transportama is a company engaged in the field of Freight forwarder and warehousing services. PT. Big Ocean Transportama realizes the importance of making improvements and increasing warehousing services, namely by comparing warehousing services in companies engaged in the warehousing service business, namely PT. Buana Jaya Cargo and PT. Cipta Krida Bahari as an effort to respond to changes and improvements optimally both internally and externally and to improve the quality of warehousing services. With this description, the author is very interested in studying it in more depth and pouring it into a Journal with the title